Research Progress of DNA Methylation in Fish - Hai HUANG; Yan LU; Liu CAO (Progress in Fishery Sciences)
DNA methylation is an important epigenetic regulatory mechanism in organisms that regulates genome stability through chromosome and protein structures without altering gene sequences. DNA methylation has been applied in the fields of medicine, agriculture, forestry and animal husbandry, and has attracted great attention in the field of fish genetics and fish breeding.Methyl groups are transferred to cytosine residues by specific DNA methyltransferases in fish DNA molecules, such as DNMT3, and the existing DNA methylation cell patterns are maintained by the methylation maintenance enzyme, DNMT1. Finally, the methyl group is removed by the oxidation of ten-eleven translocation dioxygenase (Tet1/2/3). DNMT2 catalyzes the transfer of methyl groups from the cofactor S-adenosylmethionine (SAM) to carbon 5 of the cytosine residues of the cytoplasmic tRNA—SAM is also converted to S-adenosine homocysteine. These DNA methylated transferases are widely present in many cells and tissues and play an important role in fish. DNA methyltransferase catalyzes the transfer of methyl groups from SAM to biomolecules (DNA, RNA, proteins, and small molecules) in vivo. There are many species of fish DNA methyltransferases, including two homologous DNMT1 enzymes (DNMT1a and DNMT1b), one DNMT2 enzyme, and eight homologous DNA methyltransferase 3. The naming of DNA methyltransferase 3 homologous genes is complicated; however, they are all parologous genes of DNMT3a and DNMT3b. Demethylation refers to the demethylase-mediated removal of methyl groups from DNA, which plays a key role in gene expression regulation, cell differentiation, embryonic development, and disease occurrence and development.Demethylation refers to the removal of methyl groups from DNA by demethylases. DNA demethylation patterns can be divided into passive and active DNA demethylation patterns. In passive demethylation, methylated DNA undergoes demethylation in successive replication cycles by inactivation or nuclear rejection of DNA methylation transferases that maintain methylation patterns, as well as ubiquitin-like proteins containing PHD and RING finger domains1 (uhrf1). In active DNA demethylation, methylcytosine is first oxidized by TET1/2/3 and then excised by thymine DNA glycosylase. During this process, DNA 5-methylcytosine is oxidized to 5-hydroxymethylcytosine. These oxidation products act as intermediates in DNA demethylation and are replaced by unmodified cytosines to achieve demethylation.The biological function of DNA methylation in fish is similar to that observed in other organisms, such as mammals, and is involved in gene regulation and cell development. DNA methylation occurs in three C environments: CG, CHG, and CHH (where H is any basic group other than G). DNA methylation occurs primarily at the CG site and allows fish to precisely regulate gene expression and adapt to different environmental factors. Differential methylation—cytosine-phosphate-guanine sites—is involved in apoptosis, epigenetic regulation, autophagy, collagen metabolism, cell membrane function, and homeobox protein generation through gene expression regulation. DNA methylation leads to changes in DNA conformation and stability, and the manner in which DNA interacts with RNA (or proteins) to control gene expression. It can interact with its binding proteins to inhibit gene expression in fish.DNA methylation affects genome expression regulation by activating or inhibiting transcription at the transcriptional level. Methylation near the transcriptional initiation site blocks initiation, but in the gene body it does not block and may even stimulate transcriptional elongation. It plays an important role in fish biological functions—gene expression regulation, embryonic development, reproductive development, muscle growth, body color, disease, and evolution. It can also provide insights into how genes are regulated during development and how these patterns are passed on to future generations, contributing to the understanding of epigenetics.Fish are often used as model organisms in endocrine disruption studies because of their high sensitivity to environmental factors. Environmental factors—temperature, heavy metals, starvation stress, nutritional feed, and hormones—affect the regulation of DNA methylation in fish, affecting their growth, development, and overall health.Recently, DNA methylation has attracted increasing attention as an important epigenetic regulator. The pattern and biological function of DNA methylation in fish, as well as its relationship with important environmental factors, have been gradually recognized; however, knowledge of its depth and breadth are insufficient. For example: (1) because of the wide variety of fish species, their DNA methylation characteristics still need researching; (2) there are still many important epigenetic relationships between DNA methylation, and more genes associated with it need to be explored to improve the application efficiency of fish breeding; (3) the specific mechanisms of some important variations and DNA methylation levels are still unclear; (4) the genetic mechanism of DNA methylation levels in different generations is still unclear; and (5) the interaction of core regulators of DNA methylation and the regulation and differentiation mechanisms are not clear. Further studies of these scientific issues will reveal the mechanism of fish methylation regulation of growth and development and the environmental factor response mechanisms, enrich the theoretical system of fish epigenetics, and provide a theoretical basis for the application of genetic breeding.